(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Arecanut is the chief component of the betel quid commonly used for chewing. Ayurvedic preparations containing Areca catechu were used to treat a variety of ailments. The Areca catechu plant was believed to possess many phytoactive components, which contributed to its medicinal use. Objective: The present study aimed at evaluating the phytochemical constituents of the hydroalcoholic extract of tender areca nut (6-7 months) by preliminary qualitative and quantitative estimation by the high-performance thin layer chromatography (HPTLC) method. Methods: The tender arecanut was collected from the coastal region of Karnataka and removed from adulterants, then dried and sliced. The extract was prepared by the cold maceration method at a 1:1 concentration of water and ethanol. The extract was analysed for its preliminary phytochemical analysis using standard procedures. Quantitative analysis of the active phytochemical was done using the HPTLC method to separate the various active components based on their Rf values, and densitogram analysis was done using a CAMAG TLC scanner 3 linked to WINCAT software to detect the concentration of each phytoconstituent. Results: The preliminary qualitative methods of analysis showed the presence of many phytoactive constituents. There were nine active phytoconstituents separated by HPTLC, and concentrations were estimated as percentages. Conclusion: The nine different phytoactive constituents separated from the plant's extract support the medicinal property of the plant.